Addiction and the Brain-Disease Fallacy - Sally eSatel; Scott O. Lilienfeld (Frontiers in Psychiatry, 2014)
The notion that addiction is a ''brain disease'' has become widespread and rarely challenged.The brain disease model implies erroneously that the brain is necessarily the most important and useful level of analysis for understanding and treating addiction. This paper will explain the limits of over-medicalizing -- while acknowledging a legitimate place for medication in the therapeutic repertoire -- and why a broader perspective on the problems of the addicted person is essential to understanding addiction and to providing optimal care. In short, the brain disease model obscures the dimension of choice in addiction, the capacity to respond to incentives, and also the essential fact people use drugs for reasons (as consistent with a self-medication hypothesis). The latter becomes obvious when patients become abstinent yet still struggle to assume rewarding lives in the realm of work and relationships. Thankfully, addicts can choose to recover and are not helpless victims of their own ''hijacked brains.''